Evaluation of the Model Regulation of Home Ownership Financing Based on Islamic Sharia in Accommodating PPR of Islamic Banks and Non-Banks - Maripah, Emma; Firmansyah Pratama Alim; Ika Rahmaningtyas (Universitas Djuanda, 2026)
The research discusses the evaluation of Home Ownership Financing (PPR) regulations in terms of sharia compliance, the availability of regulations, and the relevance of technical operational implementation in accordance with sharia principles. Sharia PPR is implemented through Sharia Banks and non-banks implemented by sharia developers. The challenge is that there are discrepancies in its implementation, both sharia, legal, and operational. This condition opens up opportunities for the development of non-bank Sharia PPR, which is carried out by sharia developers, to carry out different Sharia PPR schemes, through access to more sharia and easier financing, because without BI checking, without banks, without false contracts, and claimed to be free from elements of maisir, gharar, and usury. This scheme is an attraction for the public to access non-bank Islamic PPR. The problem is that non-bank Sharia PPR still has various weaknesses. Among them, there is no supervision from DSN-MUI or OJK. There is no regulation underlying its implementation. This research explores potential improvements to the regulatory model of Islamic PPR for both banks and non-banks, by analyzing regulations, including Law No.11 of 2013 concerning PUPR, Law No. 21 of 2008 concerning Islamic Banking, POJK No. 12 of 2023, as well as the fatwa of the Indonesian Ulema Council (MUI). It is expected to provide critical analysis in an effort to improve the practice of Sharia PPR. In addition, the importance of legal certainty, development of regulatory models, financing, and various innovations for the implementation of kaffah Sharia PPR. The recommendation is to carry out a revision of the current regulation, as well as the formation of a special regulation for Islamic PPR which is expected to become a legal umbrella for the implementation of PPR for Islamic banks and non-banks. Thus, the effectiveness of the regulation can be achieved and public access to Islamic PPR can be further expanded.